Osteoblast-restricted Disruption of the Growth Hormone Receptor in Mice Results in Sexually Dimorphic Skeletal Phenotypes - Singhal, Vandana (Bone Res, 2013)
Growth hormone (GH) exerts profound anabolic actions during postnatal skeletal development, in part, through stimulating the production of insulin-like growth factor-1 (IGF-1) in liver and skeletal tissues. To examine the requirement for the GH receptor (GHR) in osteoblast function in bone, we used Cre-LoxP methods to disrupt the GHR from osteoblasts, both in vitro and in vivo. Disruption of GHR from primary calvarial osteoblasts in vitro abolished GH-induced signaling, as assessed by JAK2/STAT5 phosphorylation, and abrogated GH-induced proliferative and anti-apoptotic actions. Osteoblasts lacking GHR exhibited reduced IGF-1-induced Erk and Akt phosphorylation and attenuated IGF-1-induced proliferation and anti-apoptotic action. In addition, differentiation was modestly impaired in osteoblasts lacking GHR, as demonstrated by reduced alkaline phosphatase staining and calcium deposition. In order to determine the requirement for the GHR in bone in vivo, we generated mice lacking the GHR specifically in osteoblasts (ΔGHR), which were born at the expected Mendelian frequency, had a normal life span and were of normal size. Three week-old, female ΔGHR mice had significantly reduced osteoblast numbers, consistent with the in vitro data. By six weeks of age however, female ΔGHR mice demonstrated a marked increase in osteoblasts, although mineralization was impaired; a phenotype similar to that observed previously in mice lacking IGF-1R specifically in osteoblasts. The most striking phenotype occurred in male mice however, where disruption of the GHR from osteoblasts resulted in a “feminization” of bone geometry in 16 week-old mice, as observed by μCT. These results demonstrate that the GHR is required for normal postnatal bone development in both sexes. GH appears to serve a primary function in modulating local IGF-1 action. However, the changes in bone geometry observed in male ΔGHR mice suggest that, in addition to facilitating IGF-1 action, GH may function to a greater extent than previously appreciated in establishing the sexual dimorphism of the skeleton.